ABC Drug Transporters as Molecular Targets for the Prevention of Multidrug Resistance and Drug-Drug Interactions - Calcagno, Anna M.; Kim, In-Wha; Wu, Chung-Pu; Shukla, Suneet; Ambudkar, Suresh V. (Current Drug Delivery, 2007)
ABC transporters play an important role in mediating the cytoplasmic concentration of endogenous and xenobiotic substances. They therefore influence the pharmacokinetic profile of a variety of drugs. By virtue of their localization to plasma membranes in the intestine, liver, blood-brain and other vital biological barriers, a majority of ABC drug transporters cause drug-drug interactions, decreased drug efficacy and multidrug resistance for chemotherapeutic agents. Thus, elucidating which drug entities are substrates for ABC drug transporters is a crucial step in the drug development and treatment process. Here, we review the current status of methodology used to categorize drug compounds as substrates or modulators for the major ABC drug transporters including ABCB1, ABCC1 and ABCG2.
Keywords: photoaffinity labeling